2014
DOI: 10.1371/journal.pone.0092427
|View full text |Cite
|
Sign up to set email alerts
|

Shear Stress Induced by an Interstitial Level of Slow Flow Increases the Osteogenic Differentiation of Mesenchymal Stem Cells through TAZ Activation

Abstract: Shear stress activates cellular signaling involved in cellular proliferation, differentiation, and migration. However, the mechanisms of mesenchymal stem cell (MSC) differentiation under interstitial flow are not fully understood. Here, we show the increased osteogenic differentiation of MSCs under exposure to constant, extremely low shear stress created by osmotic pressure-induced flow in a microfluidic chip. The interstitial level of shear stress in the proposed microfluidic system stimulated nuclear localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(135 citation statements)
references
References 41 publications
6
129
0
Order By: Relevance
“…Mechanical stress is known to stimulate MSC differentiation [163][164][165]. In general, high tensile stress is associated with tenogenesis and low tensile stress with osteogenesis, while compressive loading is associated with chondrogenesis [166].…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…Mechanical stress is known to stimulate MSC differentiation [163][164][165]. In general, high tensile stress is associated with tenogenesis and low tensile stress with osteogenesis, while compressive loading is associated with chondrogenesis [166].…”
Section: Mechanical Stimulationmentioning
confidence: 99%
“…Accumulating evidence has shown that mechanical factors, such as fluid shear stress, mechanical strain and the rigidity of the extracellular matrix, can regulate the proliferation and differentiation of BMSCs. It has been proven that both shear stress (Kim et al, 2014) and cyclic stretching (Kang et al, 2012;Kearney et al, 2010) could increase the expression of osteogenic markers. Cyclic stretching also serves as a driving factor for promoting the expression of genes related to smooth muscle cells (SMCs) in BMSCs (Hamilton et al, 2004;Park et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of Cyr61/CCN1 is known to be activated in response to mechanical stress at the transcriptional level (6) in several kinds of cells, such as fibroblasts (40), smooth muscle cells (13) in vitro, and skeletal muscle in vivo (20). With regard to bone cells and MSCs, only in vitro studies with shear stress have reported the upregulation of Cyr61/CCN1 (19,21,48). This is the first study to show the stimulated expression of Cry61/CCN1 with mechanical tensile stress in the cranial suture tissue where intramembranous ossification is under progress.…”
Section: Discussionmentioning
confidence: 99%